Overexplicit Referent Tracking in L2 English: Strategy, Avoidance, or Myth?. Issue 4 (8th October 2015) - Ryan, Jonathon
<x xml:space="preserve">Abstract</x> The tendency of intermediate and advanced second language speakers to underuse pronouns and zero anaphora has been characterized as a developmental stage of overexplicitness, yet little consideration has been given to whether learners create sufficient contexts for their use. This study analyzed references across eight degrees of accessibility, revealing that this did not account for infrequent pronoun use by Chinese learners of English. Further analysis revealed that participants were seldom overexplicit when referring to highly accessible individuals, particularly those that represented continued topics, but were significantly more likely than native speakers to use lexical noun phrases elsewhere, particularly for main characters. This is discussed in relation to a possible role of overexplicitness as a clarity‐based communication strategy.